Varicella-zoster virus complements herpes simplex virus type 1 temperature-sensitive mutants. - Felser, J M (1987)
Varicella-zoster virus (VZV) can complement temperature-sensitive mutants of herpes simplex virus. Of seven mutants tested, two, carrying mutations in the immediate-early ICP4 and ICP27 proteins, were complemented. This complementation was not seen in coinfections with adenovirus type 5 or cytomegalovirus. Following transfection into CV-1 cells, a DNA fragment containing the VZV short repeat sequence complemented the ICP4 mutant. These data demonstrate a functional relationship between VZV and herpes simplex virus and have allowed localization of a putative VZV immediate-early gene.